The development of MOFs-based nanomaterials in heterogeneous organocatalysis - Liu, Xiaomei; Tang, Bing; Long, Jilan; Zhang, Wei; Liu, Xiaohong; Mirza, Zakaria (Science bulletin, 2018)
Metal-organic framework (MOF) is a class of inorganic-organic hybrid material, which has been widely used in a variety of areas. In this review, we summarized the main applications and preparation strategies of MOFs-based catalysts in heterogeneous organocatalysis. Moreover, the applications of MOFs in photocatalysis and electrocatalysis frontiers have also been mentioned in the application prospects section. Finally, the main challenges of MOFs-based catalysts that should be conquered in future are briefly sketched in the final section. [Display omitted] Metal-organic framework (MOF) is a class of inorganic-organic hybrid material assembled periodically with metal ions and organic ligands. MOFs have always been the focuses in a variety of frontier fields owing to the advantageous properties, such as large BET surface areas, tunable porosity and easy-functionalized surface structure. Among the various application areas, catalysis is one of the earliest application fields of MOFs-based materials and is one of the fastest-growing topics. In this review, the main roles of MOFs in heterogeneous organocatalysis have been systematically summarized, including used as support materials (or hosts), independent catalysts, and sacrificial templates. Moreover, the application prospects of MOFs in photocatalysis and electrocatalysis frontiers were also mentioned. Finally, the key issues that should be conquered in future were briefly sketched in the final parts of each item. We hope our perspectives could be beneficial for the readers to better understand these topics and issues, and could also provide a direction for the future exploration of some novel types of MOFs-based nanocatalysts with stable structures and functions for heterogeneous catalysis.